2018
DOI: 10.4269/ajtmh.17-0551
|View full text |Cite
|
Sign up to set email alerts
|

Enteroparasites in Preschool Children on the Pacific Region of Nicaragua

Abstract: The aim of this study was to determine for the first time the prevalence of enteroparasites in preschool children originating from the seven departments of the Pacific region in Nicaragua. One stool sample of each of 1,217 children, from 6 months to 5 years of age, was collected and personal data were recorded on delivery of the container. Samples fixed in 10% formalin were processed by a formol-acetate concentration and a modified Ziehl-Neelsen technique. The overall prevalence of enteroparasite infections wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
1
0
1
Order By: Relevance
“…The increase in G. duodenalis infection prevalence with increasing age is consistent with findings of studies carried out in preschool children in various countries [ 27 ]. The increased prevalence with age was reported to be potentially related to a child’s personal autonomy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in G. duodenalis infection prevalence with increasing age is consistent with findings of studies carried out in preschool children in various countries [ 27 ]. The increased prevalence with age was reported to be potentially related to a child’s personal autonomy.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas children from 1 to 2 years of age are under surveillance most of time, those from 3 to 5 years old start to have more autonomy and are subject to less surveillance which may imply a decrease in the adoption of good hygienic practices. Consequently, older children are likely to be more exposed to risk factors and more often infected than their younger peers [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The score was given as 20% for Yes, 10% for can't tell, and 0% for No. Eight studies were given the highest score of 100% [6], [14], [15], [16], [17], [18], [19], [20], four studies were given 80% score [21], [22], [23], [24], and one study was given a score of 70% [7]. One author in the team cross-checked the findings of the evaluation.…”
Section: Systematic Searching Strategiesmentioning
confidence: 99%
“…A total of eight studies reported on a social background as risk factors for helminth infection among urban children. Four studies identified age as a risk factor related to intestinal helminth infection [15], [17], [23], [24]. Three studies reported males to represent a higher infection rate than females [6], [15], [23], while two studies reported the higher infection were among females [17], [24].…”
Section: Prevalence the Themes And Sub-themesmentioning
confidence: 99%
“…Estima-se que 200 milhões de crianças na idade pré-escolar de todo o mundo sejam afetadas por enteroparasitas, devido à falta principalmente de estratégias de melhoramento do nível socioeconômico da população. (Muñoz-Antoli et al, 2018). No Brasil é alta a prevalência em crianças em idade escolar, a infecção por essas enteroparasitoses prejudica seu desenvolvimento físico, afetando o estado nutricional e consequentemente o rendimento escolar.…”
Section: Introductionunclassified